The inhibitory effect of Lactobacillus on siderophore production in Pseudomonas aeruginosa (in vitro). - Ali Murtatha Hasan (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2018)
Probiotic are alive microorganisms presented in food and dietary supplements, probiotics beneficially affect the individual by improving the intestinal microbial balance properties . This study revealed anew pathway of siderophore attenuation in Pseudomonas aeruginosa, using Lactobacillus. Out of forty P. aeruginosa isolates , 20 isolates were siderophore produced , Cell free supernatant (CFS) and Cell free culture (CFC) of Lactobacillus the antimicrobial agent were able to produce zones of inhibition against P. aeruginosa growth in average (8-15 mm) and (9-15 mm) by CFS and CFC respectively .These antimicrobial agent also were able to attenuate the pathogenicity of P. aeruginosa by prevent its ability to siderophore production.